Foundations of Materials Science and Engineering - Smith, William F.; Hashemi, Javad (McGraw-Hill Education, 2023)
To prepare materials engineers and scientists of the future, Foundations of Materials Science and Engineering is designed to present diverse topics in the field with appropriate breadth and depth. The strength of the book is in its focus on key concepts in science of materials (basic knowledge) followed by application of scientific principles in selection and engineering of materials (applied knowledge). This textbook is suitable for both an introductory course in materials at the sophomore level and a more advanced (junior/senior level) second course in materials science and engineering.